Model for studying commodity bundling with a focus on consumer preference: Evidence from the Korean telecommunications market. (April 2016) - Shin, Jungwoo; Choi, Jae Young; Lee, Daeho
This research complements the demand-side analysis of previous commodity bundling studies. Most previous have researchers analyzed the effects of commodity bundling by focusing on firm behavior and have assumed a simple consumer utility that does not reflect the heterogeneity of consumer preference. However, to measure the results of competition with the bundling strategy, an analysis of commodity bundling based on consumer preference is useful. Unlike previous studies, this study proposes a model that directly analyzes consumer behavior for commodity bundling and incorporates consumer heterogeneity to measure the consumer utility derived from bundled commodities. To validate the model, we used data on service subscriptions and usage of information communication technology in Korea, including fixed phone service, mobile service, and Internet. The empirical results show that the proposed model is useful in analyzing the effects of bundling for various services and products.